Egy ezeréves műfaj születése: antik hagyomány a Cinquecento olasz utópiáiban - Róth, Márton (Antikvitás & Reneszánsz, 2018)
Ever since Thomas More’s “golden little book” was published in 1516 in Leuven, every notion of social theory and every theory of state which has projected an ideal social system to a non-existent place has been called utopia. Utopias pursuing answers to contemporary social, economic and moral questions also emerged in the struggling Italy of the XVIth century, gaining enormous popularity in the literature of the ancien régime. The goal of the present study is to describe the general characteristics of renaissance utopias and the most influential authors and works of the period – bearing in mind that the genre did not exist as a well-founded paradigm at the time. Discussing their characteristics, the study aims to pay special attention to presenting the antique authors and works inspiring this evolving genre beside the Morean tradition, as well as elements borrowed from the antiquity, which later became literary tropes.